The influence of the Tourniquet time on hematological testing for antidoping purposes - Lippi, G.; Salvagno, G. L.; Solero, G. P.; Guidi, G. C. (International Journal of Sports Medicine, 2006)
Hematological manipulation to optimize aerobic performances is a serious problem in elite and professional sports and the approach to identify blood doping is as yet challenging. In most cases, the current strategy contemplates a first stage of analysis, based on the application of arbitrary threshold for hemoglobin or hematocrit, followed by second-generation blood tests, or the adoption of an individual hematological passport. To establish the influence of preanalytical variables on the athletes' hematological profile, we compared hemoglobin, hematocrit, and reticulocytes count in 27 male professional cyclists after a mean time of 2.30 ± 0.12 tourniquet holding. Statistically significant differences were observed for hematocrit (+ 2.4 %; p < 0.001) and hemoglobin measurements (+ 1.4 %; p < 0.001), but not for the reticulocytes count (- 1.9 %; p = 0.170). In 4 out of 27 cases (15 %), the variability of the hematocrit measurement exceeded the 4.1 % desirable analytical quality specification for total error. Results of the present investigation further highlight the risk that unfulfillment of rigorous and standardized procedures for collection of blood specimens might increase the number of false positive testing and might lead to inappropriate sanctioning of a minority of clean athletes with hematocrit or hemoglobin values naturally elevated. Owing to the minor biological variability and the lesser susceptibility to variation of the preanalytical phase, the hemoglobin concentration might be a more suitable parameter than hematocrit for inclusion within laboratory testing to identify blood doping.